Irrigation with saline water and foliar application of proline in ‘All Big’sweet pepper - Lima, Geovani Soares de; Santos, João Batista dos; Anjos Soares, Lauriane Almeida dos; Gheyi, Hans Raj; Nobre, Reginaldo Gomes; Pereira, Rennan Fernandes (Comunicata Scientiae, 2017)
It is proposed in this study the evaluation of the growth and yield of ‘All Big’ sweet pepper under foliar application of proline and irrigation with saline water. The research was conducted in pots adapted as drainage lisimeters under greenhouse conditions, using an Eutrophic Entisol with sandy-loam texture in the municipality of Campina Grande, PB, Brazil. A randomized block design was used testing two levels of electrical conductivity of irrigation water - ECw (0.6 and 3.0 dS m-1) associated to four proline levels (0, 10, 20 and 30 mmol L-1). Irrigation with water with ECw= 3.0 dS m-1 negatively affected the ‘All Big’pepper growth and the stem dry mass, being the most sensitive variable; the highest values for fresh mass, number and average weight of pepper fruits were obtained when water with ECw=0.6 dS m-1 was used, with proline doses of 12.17 and 0 mmol L-1, respectively; increasing proline doses did not mitigate the deleterious effects caused by irrigation water salinity of 3.0 dS m-1 on growth and yield of ‘All Big ‘ sweet pepper.